Effect of filler content on the structure‐property behavior of poly(ethylene oxide) based polyurethaneurea‐silica nanocomposites. Issue 7 (26th July 2017) - Oguz, Oguzhan; Simsek, Eren; Kosak Soz, Cagla; Kasli Heinz, Ozge; Yilgor, Emel; Yilgor, Iskender; Menceloglu, Yusuf Z.
Abstract : Poly(ethylene oxide) (PEO) based polyurethaneurea‐silica nanocomposites were prepared by solution blending and characterized by Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, Differential Scanning Calorimetry and tensile testing. The colloidal silica nanoparticles with an average size of 50 nm were synthesized by modified Stöber method in isopropanol. Silica particles were incorporated into three cycloaliphatic polyurethaneurea (PUs) copolymers based on PEO oligomers with molecular weights of 2, 000, 4, 600, and 8, 000 g/mol. Hard segment content of PUs was constant at 30% by weight. Silica content of the PU nanocomposites varied between 1 and 20% by weight. Soft segment (SS) glass transition and melting temperatures slightly increased with increasing filler content for all the copolymers. Degree of SS crystallinity first increased with 1% silica incorporation and subsequently decreased by further silica addition. Elastic modulus and tensile strengths of PU copolymers gradually increased with increasing amount of the silica filler. Elongation at break values gradually decreased in PEO‐2000 based PU copolymer with increasing silica content, whereas no significant change was observed in PUs based on PEO‐4600 and PEO‐8000. Enhancement in tensile properties of the materials was mainly attributed to the homogeneous distribution of silica filler in polymer matrices and strong polymer‐filler interactions. POLYM. ENG. SCI., 58:1097–1107, 2018. © 2017 Society of Plastics Engineers